2018
DOI: 10.1371/journal.pbio.2005924
|View full text |Cite|
|
Sign up to set email alerts
|

Preservation of myocardial contractility during acute hypoxia with OMX-CV, a novel oxygen delivery biotherapeutic

Abstract: The heart exhibits the highest basal oxygen (O2) consumption per tissue mass of any organ in the body and is uniquely dependent on aerobic metabolism to sustain contractile function. During acute hypoxic states, the body responds with a compensatory increase in cardiac output that further increases myocardial O2 demand, predisposing the heart to ischemic stress and myocardial dysfunction. Here, we test the utility of a novel engineered protein derived from the heme-based nitric oxide (NO)/oxygen (H-NOX) family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…The depressive effects of hypoxia on embryonic mouse cardiomyocytes may be related to hypoxia-inducible factor-1 mediated sarcoplasmic reticulum Ca 2+ -ATPase downregulation (Ronkainen et al, 2011). Direct negative inotropic effects of hypoxia were corroborated in a recent study that demonstrated preservation of the RV contractile function by improved oxygen delivery to the hypoxic myocardium in lambs exposed to acute hypoxia (Boehme et al, 2018).…”
Section: Right Ventricular Systolic Functionmentioning
confidence: 79%
See 1 more Smart Citation
“…The depressive effects of hypoxia on embryonic mouse cardiomyocytes may be related to hypoxia-inducible factor-1 mediated sarcoplasmic reticulum Ca 2+ -ATPase downregulation (Ronkainen et al, 2011). Direct negative inotropic effects of hypoxia were corroborated in a recent study that demonstrated preservation of the RV contractile function by improved oxygen delivery to the hypoxic myocardium in lambs exposed to acute hypoxia (Boehme et al, 2018).…”
Section: Right Ventricular Systolic Functionmentioning
confidence: 79%
“…Application of a carbon monoxide-saturated hemoglobin-based oxygen carrier significantly improved cardiac performance in mice exposed to high-altitude (Wang et al, 2017 ). Furthermore, in lambs exposed to acute hypoxia, administration of a novel oxygen delivery biotherapeutic Omniox-cardiovascular was associated with preserved RV contractile function despite elevated PVR (Boehme et al, 2018 ). Thus, artificial oxygen carriers might be useful in improving RV function in conditions of acute hypoxia exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Future therapies could target oxygen delivery specifically to the organs most in need. For example, a bio-engineered heme-containing protein, OMX-CV, has a 10-fold higher affinity for oxygen than hemoglobin does and has been shown to selectively deliver oxygen to hypoxic tissues but not to tissues at physiologic oxygen tension rates in juvenile lambs [ 121 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…It also has a lower affinity for nitric oxide, which theoretically will not present the same hypertensive complications observed with first-generation HBOC. Similar to other blood product substitutes, the molecule is polymerized and PEGylated to prolong half-life ( 42 ). Being smaller than a red blood cell, the compound travels more easily through the microcirculation.…”
Section: Novel Blood Products/blood Product Replacementmentioning
confidence: 99%
“…Being smaller than a red blood cell, the compound travels more easily through the microcirculation. In an ovine model of myocardial injury, administration of Omniox® resulted in improved myocardial oxygenation and contractility compared to control ( 42 ).…”
Section: Novel Blood Products/blood Product Replacementmentioning
confidence: 99%